A WAYS TO FIND SOLUTIONS TO PROBLEMS ENCOUNTERED IN LEARNING GERMAN: WAYS TO FIND SOLUTIONS TO PROBLEMS ENCOUNTERED IN LEARNING GERMAN - Qarshiyeva, Ruzigul (Журнал иностранных языков и лингвистики, 2022)
This article discusses the problems encountered in learning German and the use of appropriate methods.